Respostas

2013-11-18T16:44:24-02:00
A) 3x - 40 = x - 42
   3x -x = - 42 + 40
  2x = -2
    x = -2/2 
    x = -1

b) 15 - 3x = x + 19
    -3x - x = 19 - 15
    - 4x = 4      x(-1)
      4x = -4
        x = - 4/4
        x = - 1

c) 10x - 6x +8 = x - 2x 
    10x - 6x + 2x - x = -8
   12x - 7x = - 8
    5 x = - 8
       x = - 8/5

somente a letra A e B são de a raiz -1
1 5 1
2013-11-18T16:49:49-02:00
A) 3x-40 =x-42
     3x-x  =-42+40
         2x = -2
b) 15-3x =x+19
     -3x-x = +19-15
       -4x  = 4
c)10x-6x+8 = x-2x
   10x-6x-x+2x = -8
        5x = -8
1 1 1